2006
DOI: 10.1097/01.aog.0000231721.42823.9e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Calcium Intervention on Adolescent Mothers and Newborns

Abstract: Calcium diet supplemented with dairy products during adolescent pregnancy resulted in higher maternal vitamin D and folate serum levels and higher newborn weight and bone mineralization compared with controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
1
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 32 publications
1
67
1
14
Order By: Relevance
“…En la presente investigación no se encontraron diferencias entre los valores sanguíneos de las madres adolescentes y de las madres adultas. Lo anterior difiere de lo reportado en la literatura en otros grupos poblacionales, en donde las madres adolescentes tienen una mayor pérdida de masa ósea desde el 26 (13) 49 (26) 95 (50) 21 (11) 9 (13) 18 (26) 35 (51) 7 (10) 17 (14) 31 (25) comienzo del embarazo hasta la sexta semana posparto, indicando que la prevalencia de deficiencia de vitamina D en ellas es mayor 13,[23][24][25] . En nuestro estudio se documentó que la tercera parte de las madres presentaron sobrepeso u obesidad al inicio del embarazo, lo cual se incrementó significativamente al final del mismo.…”
Section: Discussionunclassified
“…En la presente investigación no se encontraron diferencias entre los valores sanguíneos de las madres adolescentes y de las madres adultas. Lo anterior difiere de lo reportado en la literatura en otros grupos poblacionales, en donde las madres adolescentes tienen una mayor pérdida de masa ósea desde el 26 (13) 49 (26) 95 (50) 21 (11) 9 (13) 18 (26) 35 (51) 7 (10) 17 (14) 31 (25) comienzo del embarazo hasta la sexta semana posparto, indicando que la prevalencia de deficiencia de vitamina D en ellas es mayor 13,[23][24][25] . En nuestro estudio se documentó que la tercera parte de las madres presentaron sobrepeso u obesidad al inicio del embarazo, lo cual se incrementó significativamente al final del mismo.…”
Section: Discussionunclassified
“…No studies have focused specifically on vitamin D deficiency during pregnancy; the available data come from observational studies (12,13,(35)(36)(37)(38)(39)(40)(41)) and a few clinical trials of vitamin D supplementation (42)(43)(44)(45)(46)(47)(48)(49)(50) in pregnant women ranging from vitamin D deficient to sufficient. Severe vitamin D deficiency causes modest hypocalcemia and secondary hyperparathyroidism in nonpregnant adults, but no reports have documented worsening during pregnancy.…”
Section: Human Datamentioning
confidence: 99%
“…Several studies found no effect of maternal vitamin D supplementation on cord blood calcium concentrations (42,48,49), but 2 small studies in Asian women showed a small but significant increase in cord calcium concentrations (46,47). Another study compared administration of 1200 mg Ca and 10 g (400 IU) vitamin D (as dairy) or 1200 mg Ca alone (as orange juice) with placebo and found greater birth weight and total body calcium levels in the fetuses whose mothers received the dairy product but no change in other skeletal variables such as length and head circumference (50). The authors do not know whether the results were due to the dairy product's vitamin D content or its nutritional content compared with the supplement.…”
Section: Human Datamentioning
confidence: 99%
“…While the majority of the countries of Europe continent have annual rainfall ranging between 300 -800 mm, a few areas receive rainfall up to 4000 mm [36]. Though the rainfall is sufficient, it does not cause any leaching of minerals.…”
Section: Discussionmentioning
confidence: 99%